Investigation of ethics approval as part of a research integrity assessment of randomised controlled trials in COVID-19 evidence syntheses: a meta-epidemiological study - Patrick Meybohm; Stephanie Weibel; Emma Sydenham; Florencia Weber; Tamara Pscheidl (BMJ Open)
Objectives Ethical compliance of randomised controlled trials (RCTs) documented as ethics committee (EC) approval is vital for participant protection but is often overlooked by evidence synthesis producers despite regulatory mandates. We aimed to systematically assess reporting of ethics approval and informed consent (IC) in RCTs included in evidence syntheses and examined its potential impact on the study pool as part of a research integrity assessment (RIA).Design Meta-epidemiological study.Setting Assessment of ethics approval; domain 3 of the RIA tool developed for evidence syntheses.Participants/subjects COVID-19 RCTs included in evidence syntheses.Primary outcomes We extracted ethical items from study reports, that is, ethics approval statements, EC details, ethics approval numbers (ENs), IC and verified national recognition of ECs. RCTs were assessed regarding ethics approval and categorised as ‘no concern’, ‘awaiting classification’ or ‘exclude’ from the study pool. We also examined the impact of study settings on ethics approval reporting and discussed assessment reliability.Results We included 188 RCTs. 93% of primary study reports contained an ethics statement, 70% provided EC details, 44% reported EN and 91% mentioned IC. Trial registration records identified the EC in 8 RCTs and EN in 25 RCTs. Overall, 41% of RCTs reported all ethical items. Authors of 95 RCTs were contacted for missing information, yielding 22 satisfactory responses. Of the 151 RCTs with identified ECs, 88% were nationally recognised. Overall, 53% of RCTs were classified as ‘no concern’, 47% as ‘awaiting classification’ and none were excluded. Most were ‘awaiting classification’ due to reporting-related reasons. No significant differences in ethics approval reporting were observed across study settings, countries, or sample sizes.Conclusions Reporting of ethical items in RCTs remains inadequate. Including ethics approval details in reporting guidelines such as Consolidated Standards of Reporting Trials could improve this. Current under-reporting issues limit the reliability of the RIA tool’s ethics approval assessment.Protocol registration The protocol is available on OSF (https://osf.io/3bzeg).